Human Resource Management & Knowledge-Based Management -- A study of HR practices in performance-related knowledge management - Huang, KeKe (2007)
Human resource management has increasingly become to a significant part of organizational management. The existing literatures related to Strategic HRM currently are closely referred to the resource-based view of the firm to explain and analyze the correlation between human capital and the sustention of competitive advantage. In view of resource-based development under the competitive dynamic environment, the economy has changed from the product-based to mainly knowledge-based. Knowledge-related resource has become to one of the key source in managerial strategy and significantly influences organizations productivity and business performance. Accordingly, knowledge and knowledge workers are highly required by organizations to abreast with the rapid innovation of information technology. Effective knowledge management together with strategic HR practices therefore assists organizations to enhance ability to achieve expected business performance.